2019
DOI: 10.1002/jbmr.3932
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of FGF-21 Negatively Affects Bone Homeostasis in Dystrophin/Utrophin Double Knockout Mice

Abstract: Duchenne muscular dystrophy (DMD) is the most common muscular dystrophy seen in children. In addition to skeletal muscle, DMD also has a significant impact on bone. The pathogenesis of bone abnormalities in DMD is still unknown. Recently, we have identified a novel bone‐regulating cytokine, fibroblast growth factor‐21 (FGF‐21), which is dramatically upregulated in skeletal muscles from DMD animal models. We hypothesize that muscle‐derived FGF‐21 negatively affects bone homeostasis in DMD. Dystrophin/utrophin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 70 publications
(158 reference statements)
2
26
0
Order By: Relevance
“…Although the exact mechanism of how FGF21 regulates bone homeostasis is still not clear, several direct and indirect mechanisms have been proposed (Figure 2). The expression of FGFRs/β-klotho in bone tissue has not been fully established, however, a recent study on dystrophic mice demonstrated that β-klotho and FGFR expression is significantly induced in mature osteoclasts (Li et al, 2020). These data indicate that bone is a direct target of FGF21 and FGF21 may affect osteoclastogenesis in DMD.…”
Section: The Effects Of Fgf21 On Bonementioning
confidence: 99%
See 4 more Smart Citations
“…Although the exact mechanism of how FGF21 regulates bone homeostasis is still not clear, several direct and indirect mechanisms have been proposed (Figure 2). The expression of FGFRs/β-klotho in bone tissue has not been fully established, however, a recent study on dystrophic mice demonstrated that β-klotho and FGFR expression is significantly induced in mature osteoclasts (Li et al, 2020). These data indicate that bone is a direct target of FGF21 and FGF21 may affect osteoclastogenesis in DMD.…”
Section: The Effects Of Fgf21 On Bonementioning
confidence: 99%
“…Myokines are cytokines or peptides synthesized and released by muscle in response to muscular contraction or various stimuli (Pedersen et al, 2007). Under basal conditions, the expression of FGF21 is predominantly from liver and adipose tissue (Nishimura et al, 2000), however, the expression and secretion of FGF21 from skeletal muscle is significantly increased under certain conditions, such as mitochondrial dysfunction (Keipert et al, 2014;Lehtonen et al, 2016;Steele et al, 2016;Khan et al, 2017;Romanello et al, 2019), muscular dystrophy (Lovadi et al, 2017;Zhou et al, 2018;Li et al, 2020), and exercise (Ost et al, 2016;Kruse et al, 2017;Morville et al, 2018). Thus, in addition to being a hepatokine and adipokine, FGF21 is also well-established as a myokine (Pedersen and Febbraio, 2012;Itoh, 2014;Pereira et al, 2017).…”
Section: Fgf21 As a Myokinementioning
confidence: 99%
See 3 more Smart Citations